Utilization of Soft Computing for Risk Assessment of a Tunneling Project Using Geological Units - Sina Shaffiee Haghshenas; Sami Shaffiee Haghshenas; Milad Barmal; Niloofar Farzan (Salehan Institute of Higher Education, 2016)
Soft computing is one of the most efficient tools for analysing risk taking in civil engineering projects. Therefore, in this paper, using Fuzzy C-means (FCM) technique as one of the most efficient and important classification methods in the area of soft computing, risk in the tunnelling project was evaluated and analysed. For this reason, considering three mechanical and physical parameters influencing the design and execution of the tunnelling project including overburden (H), internal friction angle (Phi) and cohesion (C), geological units were classified along the project's route. The present study has been conducted on the third section of Ghomrud tunnel as one of the greatest tunnelling projects in the centre of Iran. Results obtained from the evaluation of geological units along the tunnelling project's route after the validation of drilling rate index’s results show the appropriate evaluation of the project’s risk through fuzzy clustering technique.